The dual that challenged us to a duel - carcinoma colon with retroperitoneal leiomyosarcoma with liver metastasis - diagnostic and therapeutic dilemma - Shanmugam, Subbiah; Jebasingh, Arun V.; Palanisamy, Kishore (International Surgery Journal, 2024)
The presence of multiple primary cancers involving sarcoma in a single patient was first reported as far back as in 1889. We report a case of dual malignancy including carcinoma sigmoid colon and retroperitoneal leiomyosarcoma as a rare case of dual malignancy. The presentation posed a diagnostic and therapeutic dilemma. We proceeded with laparoscopic assisted sigmoid colectomy with retroperitoneal mass excision and post-operative period was uneventful. Patient was started on gemcitabine and docetaxel regimen and on regular follow up. Because of similarity of symptoms/findings between metastatic lesions and second malignancy, it may lead to mismanagement if we are not aware. When in doubt it is better to have pathological diagnosis from every lesion to avoid inappropriate management leading to inferior oncological outcome.